2019
DOI: 10.1016/j.cemconcomp.2018.11.007
|View full text |Cite|
|
Sign up to set email alerts
|

Phosphogypsum waste lime as a promising substitute of commercial limes: A rheological approach

Abstract: This paper presents the rheological properties of three types of lime putty, specifying the influence of their origin. The study aims to compare a special lime putty prepared from phosphogypsum with a commercial lime powder and an aged lime putty. The results obtained in terms of chemical composition, crystalline structure, grain size and rheological characterization, (linear viscoelasticity, shear rate and time-dependent flow behaviour) are presented in the study. Putties studied present a similar rheological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 28 publications
2
18
0
Order By: Relevance
“…C_S and Ca_S in Table 5 are the concentrations of radionuclides obtained in the lime and calcite, respectively, generated by the treatment of PG with caustic soda. These results confirmed that the major parts of the radionuclides accumulated in the Ca containing by-products [1,30]. The concentrations in the C_S samples of the uranium series exceeded the value established by CSN (UNSCEAR, 1993) at 1000 Bq/kg [53]; therefore, both by-products were considered NORM materials and must therefore be radiologically controlled for commercial applications.…”
Section: Radiological Evolutionsupporting
confidence: 71%
See 1 more Smart Citation
“…C_S and Ca_S in Table 5 are the concentrations of radionuclides obtained in the lime and calcite, respectively, generated by the treatment of PG with caustic soda. These results confirmed that the major parts of the radionuclides accumulated in the Ca containing by-products [1,30]. The concentrations in the C_S samples of the uranium series exceeded the value established by CSN (UNSCEAR, 1993) at 1000 Bq/kg [53]; therefore, both by-products were considered NORM materials and must therefore be radiologically controlled for commercial applications.…”
Section: Radiological Evolutionsupporting
confidence: 71%
“…The main aim of this work is the characterization and control of the phases resulting from PG waste transformation by two processes: Procedure A is based on treatment with Na(OH) in which the controls were performed on the portlandite obtained as lime paste in the first phase and also in the calcite resulting from carbonation. Additionally, lime mortars were manufactured from lime paste and standardized siliceous sand to verify the behaviour once the resulting material was stabilized [30], as well as its possible viability as construction material. Procedure B is based on the reaction with the residual liquid of the aluminium industry.…”
Section: Introductionmentioning
confidence: 99%
“…These include, for instance, substantially increasing the proportion of ordinary Portland cement (OPC) in mixtures or adding other tailings, such as fly ash, waste lime and zeolite, as the hydration activators. Romero-Hermida et al [25] investigated the rheological properties and microstructures of special lime putty prepared from PG. These methods decrease the setting time and improve the mechanical property of PG-based CPB.…”
Section: Introductionmentioning
confidence: 99%
“…Soluble phosphorus and other potentially harmful elements in phosphogypsum can be leached by rainwater to form acidic wastewater, causing the serious pollution of soil and the water system [12][13][14][15][16][17][18]. Therefore, the comprehensive utilization of phosphogypsum has become an important issue for the sustainable development of the phosphorus chemical industry and environmental protection [19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%